The Impact of Written Feedback on Students’ Learning Motivation - Abdullah, Sitti Aisyah; Muhayyang, Maemuna; Korompot, Chairil Anwar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study examines the significant impact of written feedback on students' learning motivation, focusing on three key types: writing skills feedback, content feedback, and motivational feedback. Utilizing a qualitative research method, data were gathered through structured interviews with seven 8th-grade students at SMPN 18 Makassar, selected through simple random sampling. The research explores how these types of feedback contribute to students' overall academic progress and intrinsic motivation to learn. Writing skills feedback helps students identify and correct errors, enhancing the structure and quality of their written work. Content feedback ensures the clarity, completeness, and understanding of learning materials, allowing students to gain deeper insight into the subject matter. Motivational feedback, on the other hand, plays a critical role in boosting students’ self-confidence, encouraging perseverance, and fostering a positive attitude toward learning. The findings indicate that these three types of written feedback positively influence students’ learning motivation by promoting greater engagement and persistence in learning tasks. Written feedback not only aids in improving students’ writing performance but also contributes to their personal development by making the learning process more interactive and rewarding. The study concludes that the strategic use of written feedback can significantly enhance students’ learning motivation, ultimately leading to better academic outcomes.